Peningkatan Aspek Percaya Diri Anak Usia Dini Melalui Kegiatan Market Day - Aliyah, Nur; Anugrah, Yuwan Fijar; Enjang, Enjang (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
Self-confidence in early childhood is important to develop, because at this stage children are still in the process of building self-concept and independence. Lack of self-confidence can hinder their social, emotional, and cognitive development. This Market Day activity was carried out as an effort to improve the quality of learning practices related to self-confidence aspects in order to support optimal child development outcomes by being packaged through interesting and fun activities. The method used is Participant Action Research (PAR) which emphasizes the active involvement of participants in each stage of implementation in order to produce real changes in the community. The subjects in this community service activity were 21 children from students of SPS Melati II, Margasari Village. The results of this community service journal are that Market Day is an effective method in increasing self-confidence for early childhood at SPS Melati II, Margasari Village, as evidenced by changes in behavior, namely children becoming more open in interacting with peers, not feeling embarrassed when meeting new people and, daring to speak in public.